If a+b+c=0, then prove that
![{a}^{3} + {b}^{3} + {c}^{3} = 3abc {a}^{3} + {b}^{3} + {c}^{3} = 3abc](https://tex.z-dn.net/?f=+%7Ba%7D%5E%7B3%7D++%2B++%7Bb%7D%5E%7B3%7D++%2B++%7Bc%7D%5E%7B3%7D++%3D+3abc)
Answers
Answered by
1
Answer:
Step-bay-step explanation:
We know that
a^3+b^3+c^3-3abc =(a+b+c)(a^2+b^2+c^2-ab-bc-ca)
= 0 *(a^2+b^2+c^2-ab-bc-ca)
= 0
=> a^3+b^3+c^3 = 3 abc. Proved
Similar questions
Social Sciences,
6 months ago
India Languages,
6 months ago
Math,
1 year ago
English,
1 year ago
Math,
1 year ago
Biology,
1 year ago